Pengaruh Literasi Keuangan dan Sikap Keuangan terhadap Perilaku Pengelolaan Keuangan Keluarga: Studi Kasus di Desa Tegalmojo - Ilyas, M.; Muzakki, Ahmad; Billah, Zahida I’tisoma (MES Bogor, 2024)
In managing household finances, apart from household financial management behavior, financial literacy and financial attitudes are also important for families. This research aims to find out how financial literacy and financial attitudes influence family financial management behavior. This research uses a descriptive quantitative approach sourced from two data, namely primary and secondary data. The research was conducted in Tegalmojo Village with data collection using 285 questionnaires. The sampling technique was purposive sampling which was used and 100 respondents obtained questionnaires that could be used. This research uses data analysis techniques, namely multiple linear regression analysis including instrument tests, classical assumption tests, T tests, F tests, and coefficient of determination with the IBM SPSS 22 program. The results of this research show that financial literacy has a significant positive effect on family financial management behavior. and financial attitudes also have a significant positive effect on family financial management behavior. The Coefficient of Determination produces financial literacy and financial attitudes that simultaneously influence family financial management behavior.